2023
DOI: 10.21273/hortsci17286-23
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse Is an Effective Soilless Substrate Amendment in Quick-turn Osteospermum Production

Maureen Thiessen,
Jeb S. Fields,
Damon Abdi
et al.

Abstract: Many greenhouse growers rely on peat-based soilless substrates to produce salable crops in a relatively short period of time. Peat-based substrate suppliers often incorporate additional organic materials such as wood fiber to extend peat supplies. Given the relative success of wood-based substrates, growing interest in other fiber materials such as sugarcane bagasse may provide similar benefits for substrate processers. The objective of this research was to evaluate substrate properties and the productivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…While the incorporation of SCB at lower percentages (15% and 30%) maintained a pH at or below that of peat in the Thiessen et al [31] study, the results of this study showed that twice as much bagasse usage maintained a pH at similar or lower levels than peat only up to 30 DAP. Similar increases in pH throughout the production process using Hydrafiber were identified when compared to bagasse when blended with a standard bagged substrate by Thiessen et al [31]. Iron deficiency is the most common disorder in petunia production and tends to occur at substrate pH levels greater than 6.4 [47]; therefore, although C and W were limed at a lower rate than P and B in this study, even lower rates may be needed to ensure proper substrate pH ranges during production.…”
Section: Greenhouse Experimentscontrasting
confidence: 57%
See 4 more Smart Citations
“…While the incorporation of SCB at lower percentages (15% and 30%) maintained a pH at or below that of peat in the Thiessen et al [31] study, the results of this study showed that twice as much bagasse usage maintained a pH at similar or lower levels than peat only up to 30 DAP. Similar increases in pH throughout the production process using Hydrafiber were identified when compared to bagasse when blended with a standard bagged substrate by Thiessen et al [31]. Iron deficiency is the most common disorder in petunia production and tends to occur at substrate pH levels greater than 6.4 [47]; therefore, although C and W were limed at a lower rate than P and B in this study, even lower rates may be needed to ensure proper substrate pH ranges during production.…”
Section: Greenhouse Experimentscontrasting
confidence: 57%
“…Similar substrate research [13,20] identified little to no difference in pH in coir substrates over peat. Sugarcane bagasse has an inherently lower pH and has previously shown the capacity to mitigate rising pH in production systems with high pH and alkalinity irrigation water [31]. While the incorporation of SCB at lower percentages (15% and 30%) maintained a pH at or below that of peat in the Thiessen et al [31] study, the results of this study showed that twice as much bagasse usage maintained a pH at similar or lower levels than peat only up to 30 DAP.…”
Section: Greenhouse Experimentsmentioning
confidence: 53%
See 3 more Smart Citations